2018
DOI: 10.3389/fpubh.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Monkeypox as the Most Important Orthopoxvirus Infection in Humans

Abstract: Monkeypox is an emerging zoonotic disease recognized as the most important orthopoxvirus infection in humans in the smallpox post-eradication era. The clinical presentation of monkeypox is similar to the one of smallpox. The case fatality rate of monkeypox (10%) lies between the case fatality rate of variola major (30%) and variola minor (1%). The disease is endemic in the Democratic Republic of the Congo, but other countries of Central and West Africa either reported cases of monkeypox in humans or circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
579
0
33

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(682 citation statements)
references
References 61 publications
2
579
0
33
Order By: Relevance
“…The monkeypox virus was first discovered in 60 years ago (von Magnus et al, 1959) and continues to remain on the radar of WHO since then (Heymann et al, 1998;Breman et al, 1980;WHO, 1984;WHO, 2018a,b). This zoonotic infection remains endemic to Central and West Africa in animal(s) reservoir(s), with increasing numbers of human cases and outbreaks being reported (Sklenovska and van Ranst, 2018;Hoff et al, 2017;Learned et al, 2005;Durski et al, 2018a;Yinka-Ogunleye et al, 2018). Monkeypox is caused by a double stranded DNA virus which belongs to the Orthopoxvirus genus of the family Poxviridae family (WHO, 2018a,b;CDC, 2018;Shchelkunov et al, 2001).…”
Section: First Discovery and Animal Host Reservoirmentioning
confidence: 99%
See 2 more Smart Citations
“…The monkeypox virus was first discovered in 60 years ago (von Magnus et al, 1959) and continues to remain on the radar of WHO since then (Heymann et al, 1998;Breman et al, 1980;WHO, 1984;WHO, 2018a,b). This zoonotic infection remains endemic to Central and West Africa in animal(s) reservoir(s), with increasing numbers of human cases and outbreaks being reported (Sklenovska and van Ranst, 2018;Hoff et al, 2017;Learned et al, 2005;Durski et al, 2018a;Yinka-Ogunleye et al, 2018). Monkeypox is caused by a double stranded DNA virus which belongs to the Orthopoxvirus genus of the family Poxviridae family (WHO, 2018a,b;CDC, 2018;Shchelkunov et al, 2001).…”
Section: First Discovery and Animal Host Reservoirmentioning
confidence: 99%
“…Several reviews have summarised human monkeypox outbreaks over the past 38 years (Rimoin et al, 2010;Sklenovská and Van Ranst, 2018;Durski et al, 2017;Durski et al, 2018b). Population-based surveillance studies conducted in nine health zones in DRC identified 760 laboratory-confirmed human monkeypox cases with an annual cumulative incidence of 5.53 per 10,000 (2.18-14.42) (Rimoin et al, 2010).…”
Section: Monkeypox Prevalence Changing Clinical Presentations and Smmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Ebola virus, Cote d'Ivoire has also been hit by monkeypox. Up to 1990, two confirmed human cases of MPXV had been reported from the country [96,97]. One common practice that has been reported from the MPXV outbreak-prone belt of the African continent is that monkeys are eaten as a delicacy, which may be a significant source of disease transmission apart from other activities, like hunting and butchering.…”
Section: Cote D' Ivoirementioning
confidence: 99%
“…Monkeypox is an endemic disease in the Democratic Republic of the Congo. The virus was also imported once into the USA (Sklenovská et al, 2018).…”
Section: Introductionmentioning
confidence: 99%